The screenplay as boundary object. (1st June 2019) - Davies, Rosamund
Described by Pasolini as a 'structure that wants to be another structure', the question of what kind of thing-in-itself the screenplay might be has produced a range of answers. Screenwriter Jean-Claude Carrière has used the metaphor of the chrysalis – of vital importance in the process of the caterpillar's metamorphosis into a butterfly – but useless and empty once the butterfly, or film, has emerged. Film scholar Claudia Sternberg has considered the screenplay's status as a 'second rank' text, in relation to the 'first rank' film performance. The idea of the screenplay as blueprint is common. Meanwhile, scholars (e.g. Maras, Millard, Price) have raised issues with such definitions, pointing out their limitations. In this article, I propose the notion of the 'boundary object' as a useful way of thinking about the role and nature of the screenplay within the development and production of a screen narrative. My starting point is sociologist Susan Leigh Star's concept of the boundary object, defined as an object that allows different individuals or groups with heterogeneous skills, knowledge and interests to cooperate towards a common goal by creating a 'shared space', situated at the boundaries between their habitual spheres of practice. I propose that, avoiding the problems inherent in an analogy such as the blueprint, the concept of the boundary object offers a useful starting point for understanding and analysing the role of the screenplay in audio-visual production.